Primary diffuse large B-cell lymphoma of the prostate: Histopathological diagnosis of a rare entity in the prostate - Richa Sharma; Sumit Bansal; Aparna Gangoli (Indian Journal of Pathology and Microbiology)
Lymphoma of the prostate is rare whether it is primary extranodal lymphoma or secondary involvement of the prostate by primary lymphoma elsewhere. Of all the lymphomas of the prostate, primary lymphomas of the prostrate are very rare. Although less frequent, it should be a differential diagnosis when evaluating prostate tumors. Here, we report a case of a 61-year-old man who presented with hematuria with clot retention. A cystoscopy with clot removal and transurethral resection of the prostate (TURP) was performed. This biopsy was sent for histopathological examination at an external center, where a diagnosis of benign prostatic hyperplasia was given. Fifteen days later, the patient presented with hematuria again. On examination, clots were present in the bladder. There was significant prostatomegaly. A re-resection of the prostate was performed and sent for another review to us. The biopsy was reported as high-grade round cell neoplasm, most likely lymphoma. Immunohistochemistry (IHC) was recommended for confirmation. Tumor cells showed immunoreactivity for CD20, B-cell Lymphoma (BCL)-2, BCL-6, Myelocytomatosis (c-Myc), and multiple myeloma 1 (MUM1). Cluster Differentiation (CD)10 was negative. Kiel-67 was high. A final diagnosis of double-expressor diffuse large B-cell lymphoma (DLBCL) of non-germinal center type was made. We share this case to emphasize the fact that primary lymphoma of the prostate is primarily a histopathological diagnosis as the clinical presentation is not unique. Owing to its rarity, the clinical and histopathological suspicion is low. Hence, keeping the differential in mind while evaluating prostate biopsy is beneficial in a timely diagnosis of the entity as the management of prostatic carcinoma and lymphoma is different.